Questioni kantiane - Carrano, Antonio (Scuola di Scienze Umane e Sociali. Quaderni, 2022)
Here are collected five essays where themes concerning ethics, aesthetics and philosophy of religion are examined, which have their ideal reference in the problem of the edification of the human, of which Kant understood the idea in dynamic terms, as suggested by the concept of 'destination' as well as the program of a 'reform of the way of thinking'. Producing this change was a non-secondary aim of a philosophy that, in the spirit of modern reflexivity, had the pride of calling itself "critical", firm in the intention of reconciling the different needs of reason.